Global Disparities in Breast Cancer Genetics Testing, Counselling and Management - Yip, Cheng Har; Evans, Dolores Gareth; Agarwal, Gaurav; Buccimazza, Ines; Kwong, Ava; Morant, R.; Prakash, Ipshita; Song, C.Y.; Mohd Taib, Nur Aishah; Tausch, Christoph; Ung, Owen; Meterissian, Sarkis (Springer Verlag (Germany), 2019)
Hereditary breast cancers, mainly due to BRCA1 and BRCA2 mutations, account for only 5–10% of this disease. The threshold for genetic testing is a 10% likelihood of detecting a mutation, as determined by validated models such as BOADICEA and Manchester Scoring System. A 90–95% reduction in breast cancer risk can be achieved with bilateral risk-reducing mastectomy in unaffected BRCA mutation carriers. In patients with BRCA-associated breast cancer, there is a 40% risk of contralateral breast cancer and hence risk-reducing contralateral mastectomy is recommended, which can be performed simultaneously with surgery for unilateral breast cancer. Other options for risk management include surveillance by mammogram and breast magnetic resonance imaging, and chemoprevention with hormonal agents. With the advent of next-generation sequencing and development of multigene panel testing, the cost and time taken for genetic testing have reduced, making it possible for treatment-focused genetic testing. There are also drugs such as the PARP inhibitors that specifically target the BRCA mutation. Risk management multidisciplinary clinics are designed to quantify risk, and offer advice on preventative strategies. However, such services are only possible in high-income settings. In low-resource settings, the prohibitive cost of testing and the lack of genetic counsellors are major barriers to setting up a breast cancer genetics service. Family history is often not well documented because of the stigma associated with cancer. Breast cancer genetics services remain an unmet need in low- and middle-income countries, where the priority is to optimise access to quality treatment.